Diseño de un sistema de protección contra incendio en una planta envasadora de gas licuado de petróleo - Anchundia V., Fernando (2010)
This work intends to serve as reference to those people that they wish to have an overview of the process of design of a Fire Protection System for a Plant bottler of Liquefied Petroleum Gas. The objective of the project is than next the enlargement of this plant bottler, count on a system against efficacious fire and obey the normative applicable requirements. The design is based on the present-day analysis that was had you plant it before the enlargement to present at a later time calculations and criteria of selection for the new installed capacity, that NFPA comprises the storage tanks, system of pumping, hydraulic net and methods of suppression, according to the national regimentation, Standards; with equipment, accessories and available hand of qualified work in the local market. The feasibility of the project justifies itself when presenting the cost analysis between a system of pumping certified by NFPA and a puttogether one locally, that also you obey those international standards. Finally you encounter recommendations for an